Phenotypic and genetic analysis of grain elongation trait for high quality rice / Syahidah Sulaiman - Sulaiman, Syahidah (2018)
A high quality rice is defined by good aroma, long grain and moderate amylose content. Thus, the purpose of this study are to determine the grain elongation trait of rice samples from the local market and selected varieties. Together with the phenotypic variation of grain elongation trait especially on elongation ratio and alkali spreading value. The effects of artificial and natural ageing also determined on the selected rice varieties. Rice samples were bought from local market. And paddy varieties were obtained from MARDI Genebank Seberang Prai, Penang. From the results obtained, selected varieties were treated under artificial and natural ageing condition. The best artificial ageing is at the range of 1-3 hours and temperature between 100°C-120°C. Furthermore, natural ageing at third month resulted in the highest elongation ratio compared to other storage duration. Lastly, selected varieties were used as parental materials to breed local variety with elongation trait. Normal rice elongates at elongation ratio of 1.4 whereas special quality rice usually elongates more than 1.6, and often reach more than 2.0. Inheritance study was conducted on the elongation ratio in 4 crosses of F2 generations namely; MRQ74/MR219, MRQ76/MR219, Mahsuri Mutant/MR219 and Basmati 370/MR219. From the observed grains elongation ratio of all the 4 crosses, all the ratio fulfilled the expected ratio of 3:1 in F2 generations. Additional observation from the score of alkali spreading value in the F2 generations showed that all grains after 23 hours being soaked in the alkali solution in the MRQ74/MR219 and Basmati 370/MR219 were low ASV and high GT. While grains from MRQ76/MR219 and Mahsuri Mutant/MR219 crosses were in high ASV and low GT.